The Impact of Formal and Legal Conditions on Environmental Disclosures in the ESG Framework by Capital Groups in the Hard Coal Mining Sector: Evidence from Poland - SULIK-GÓRECKA (Acta Montanistica Slovaca, 2025)
The extraction of hard coal has significant adverse effects on the natural environment, which mining entities disclose in their non-financial reports in compliance with increasingly stringent legal regulations. Regular stakeholder communication, encompassing comprehensive information on a company's economic, social, and environmental activities, enhances corporate transparency, facilitates the assessment of strategic implementation, and supports the identification of future risks. The objective of this article is to assess the impact of formal and legal conditions on ESG reporting within the environmental disclosure domain by the largest capital groups in Poland's hard coal mining sector over the period 2017–2024, with a particular focus on the role of taxonomy reports. The study employs an in-depth qualitative comparative analysis of data contained in the Management Board's activity reports and the consolidated financial statements of the three largest capital groups in the hard coal mining sector: the Jastrzębska Spółka Węglowa (JSW) Group, the Lubelski Węgiel Bogdanka S.A. (LWB) Group, and the Polska Grupa Górnicza S.A. (PGG). The comparative findings of these three capital groups – two of which are publicly listed on the Warsaw Stock Exchange (GPW) and one that remains privately held and subject to the Polish Accounting Act – revealed significant differences in the scope of environmental disclosures within the ESG framework. The primary reason for these differences lies in the varying ESG reporting regulations applicable to publicly traded groups. The study's results indicate that due to the classification of their operations as non-sustainable under the EU Taxonomy, the ESG indicators reported by the publicly listed companies are notably low, as coal extraction and sales are not considered sustainable activities. However, a detailed analysis of the companies' activity reports highlights substantial engagement in pro-environmental initiatives, reflected in expenditures, costs, and investments related to environmental protection. The study's findings contribute to a deeper understanding of the specific characteristics of the hard coal mining sector in the context of ESG reporting, offering insights into the implications of regulatory frameworks on corporate disclosure practices.